1997
DOI: 10.1172/jci119541
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine-dependent gp130 receptor subunit regulates human fetal pituitary adrenocorticotropin hormone and growth hormone secretion.

Abstract: We have shown recently that leukemia inhibitory factor (LIF) and oncostatin M (OSM), two members of the gp130-dependent cytokine family, stimulate murine proopiomelanocortin (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 57 publications
2
40
0
Order By: Relevance
“…Their effects may result from direct action on the gastrointestinal system or indirect effects mediated by cytokines (ILβ-1, IL-2, IFN-γ and TNF-α) on the central nervous system. 12,[27][28][29][30][31][32][33] Cytokines can also interact with prostaglandins (members of a group of lipid compounds that are derived enzymatically from fatty acids and have important functions in the body) and corticotrophin-releasing hormone (CRH), a polypeptide hormone and neurotransmitter involved in the stress response to inhibit gastric emptying. 29,30 Cytokine interaction with neuropeptides may induce anorexia and can also modify serotonin and catecholamine pathways in the central and peripheral nervous system.…”
Section: The Role Of Cytokinesmentioning
confidence: 99%
“…Their effects may result from direct action on the gastrointestinal system or indirect effects mediated by cytokines (ILβ-1, IL-2, IFN-γ and TNF-α) on the central nervous system. 12,[27][28][29][30][31][32][33] Cytokines can also interact with prostaglandins (members of a group of lipid compounds that are derived enzymatically from fatty acids and have important functions in the body) and corticotrophin-releasing hormone (CRH), a polypeptide hormone and neurotransmitter involved in the stress response to inhibit gastric emptying. 29,30 Cytokine interaction with neuropeptides may induce anorexia and can also modify serotonin and catecholamine pathways in the central and peripheral nervous system.…”
Section: The Role Of Cytokinesmentioning
confidence: 99%
“…We previously demonstrated LIF to be a potent auto͞paracrine stimulus of pituitary proopiomelanocortin (POMC) gene expression and adrenocorticotropic hormone (ACTH) secretion, modulating the hypothalamus-pituitary-adrenal (HPA) axis response to various inflammatory and stress stimuli (20)(21)(22). In vitro experiments using human fetal pituitary cells (23) and the corticotroph cell line AtT-20 (24,25) showed a profound synergistic action of LIF and corticotropin-releasing hormone on POMC gene expression and ACTH secretion. The LIF-induced signaling cascade in the corticotroph cell involves phosphorylation of gp130, STAT-3, and STAT-1 (15,23,26,27), and LIF-induced POMC expression and ACTH secretion is STAT-3 dependent (28).…”
mentioning
confidence: 94%
“…gp130 expression is ubiquitous, and its ability to respond differentially to each of the proteins that belong to the gp130 cytokine family is determined by the expression of the cytokines or their specific alpha receptor chains. This occurs also in the pituitary gland, where many studies have demonstrated not only the expression of gp130 mRNA (6) but also the expression of specific receptors and synthesis of gp130 cytokines in different types of pituitary cells (reviewed in [7][8][9][10], providing the cellular and molecular basis for an auto-paracrine mechanism of regulation of pituitary function. Particularly, several groups have demonstrated IL-6 production and the presence of IL-6 mRNA in anterior pituitary cells (11,12).…”
Section: Introductionmentioning
confidence: 99%